Nonrigid Medical Image Registration Based on Mesh Deformation Constraints. (2nd February 2013) - Lin, XiangBo; Ruan, Su; Qiu, TianShuang; Guo, DongMei
Abstract : Regularizing the deformation field is an important aspect in nonrigid medical image registration. By covering the template image with a triangular mesh, this paper proposes a new regularization constraint in terms of connections between mesh vertices. The connection relationship is preserved by the spring analogy method. The method is evaluated by registering cerebral magnetic resonance imaging (MRI) image data obtained from different individuals. Experimental results show that the proposed method has good deformation ability and topology-preserving ability, providing a new way to the nonrigid medical image registration.